Emotional experiences beyond the classroom: Interactions with the social world - Ross, Andrew S.; Rivers, Damian J. (Studies in Second Language Learning and Teaching, 2018)
Research into the emotional experiences of language learners and their impact upon the language-learning process remains relatively undernourished within second language education. The research available focuses primarily on emotions experienced within the classroom, rather than in the daily lives of learners within various social contexts. This article contends that the focus placed upon emotions within the relatively structured environment of the formal classroom is problematic, particularly within an ESL environment, as the target language is more frequently experienced beyond the classroom. Drawing on data collected within Australia, the study explored the emotional experiences of a small cohort of eight university-level ESL learners experienced within their various social interactions beyond the classroom with a specific focus on the emotions of hope, enjoyment and frustration. Semi-structured interviews revealed that their emotional experiences beyond the classroom were particularly intense in comparison to emotional experiences within the formal language-learning classroom.